Концепции космотеории (Сообшение 12) - Суворов, Н.П. (Медична гідрологія та реабілітація, 2009)
Дана публікація є продовженням викладу погляду автора на стратегію розвитку людини. In the present publication the analysis of some methods of raise the quantity and quality of energy of the anthropological essences and systems is conducted.